High Incidence of Renal Stones in Severely Disabled Children with Epilepsy Treated with Topiramate - Ishikawa, Nobutsune; Tani, Hiroo; Kobayashi, Yoshiyuki; Kato, Akira; Kobayashi, Masao (Neuropediatrics, 2019)
Purpose This study was aimed to assess the accurate incidence of renal stones in severely disabled children treated with topiramate (TPM).Method We reviewed the medical records of severely disabled children with epilepsy under 15 years old who underwent radiological examinations to investigate urinary stones. The study enrolled 26 patients who were divided into two groups. One group had been treated with TPM for at least 1 year and the other had not been treated with TPM, zonisamide, acetazolamide, or other diuretic drugs. We collected parameters from the medical records and compared the groups.Results All participants were evaluated radiologically, with computed tomography (CT) in two patients, ultrasonography in 22 patients, and both in two. No patient had any morphological abnormality of the kidneys and history of urinary tract infection. There were no significant differences in sex, age, body weight, or feeding manner between the groups, while the incidence of renal stones or calcifications was significantly higher in the TPM-treated group (60 vs. 0%; p = 0.00241).Conclusion There is a high incidence of renal stone formation in severely disabled children treated with TPM.
Keywords: severely disabled children with epilepsy; antiepileptic drug; topiramate; renal stone; nonambulatory children